The Role of The Village Consultative Body in The Context of Supervision of The Village Government in Simpang Village, Residents Outside Aluh-Aluh District, Banjar Regency - Meikiansyah, Bachruddin; Sianturi, Hans Reyner Edison; Akmal, Akmal; Rubi, Rubi (Jurnal Indonesia Sosial Sains, 2024)
This research aims to: 1) Know and obtain data on the implementation of the function of the Village Consultative Board in the implementation of government in Simpang Village of Residents Outside Aluh-Aluh District of Banjar Regency, 2) Know and obtain data on factors that affect the implementation of the function of the Village Consultative Board in the implementation of government in Simpang Village Residents Outside Aluh-Aluh District, Banjar Regency. This research uses qualitative research with a sociological approach because data is obtained directly from facts in society—data collection through case studies, field research, and interviews. The results of this study show that: 1. Implementation of BPD Supervision Function in the implementation of government in Simpang Village of Residents Outside Aluh-Aluh District, Banjar Regency has not been thoroughly carried out optimally because only 3 (three) main tasks are carried out, namely accommodating and distributing community aspirations, 2. Factors that affect the implementation of bpd supervision function are influenced by driving factors, community support/participation in BPD, and good cooperative relations between BPD and the Village Government. At the same time, the second factor is an inhibitory factor that includes the lack of benefits given to BPD members, facilities and infrastructure, lack of human resources that fill BPD membership, and the existence of community pros and cons to every decision set.